Basic Orientations and Institutional Failures of Economic Governance in the Capitalist State - Shengsheng Wang (World Review of Political Economy)
To understand the capitalist state, often labeled as the “modern state,” it is imperative to analyze the relations of dialectical unification between the class nature of the state and its public character with the perspective of historical materialism. From the narrative logic of Capital , capitalist relations of production have a fourfold prescriptive nature that rises from the abstract to the concrete, and that endows the capitalist state with a fourfold, elastic structure: system, organization, operation, and discourse, with the result that the capitalist state acquires the false form of a defender of the public interest. The strategies of capitalist economic governance serve to embed capital accumulation in the process of expanded social reproduction, and allow it to dominate this process. Due to the historical limitations of the capitalist relations of production, however, the economic governance of the capitalist state includes a systemic boundary that cannot be crossed, and the accumulation and deepening of the contradictory movement of the aggregate social capital leads inevitably to the economic governance of the capitalist state experiencing systemic failure.